Identification of Hydrothermal Reservoirs Using the Dipole-Dipole Configuration Geoelectric Method in Air Putih Village, Lebong Regency, Bengkulu - Wahyu cahyadi setiawan wahyu; Suhendra Suhendra; Halauddin Halauddin; Muhammad Wilzam Fauzi Muhammad Wilzam Fauzi; Bayu Saputra Bayu Saputra; Sri Rahayu Sri Rahayu; Rival Zamrawi Rival Zamrawi; Bimantara Panca Utama Bimantara Panca Utama (Jurnal Fisika, 2024)
This study was conducted in Lebong Regency, Bengkulu Province, where the Ketahun segmented fault crosses. Using geoelectric data, this study was conducted to identify the distribution of hydrothermal reservoirs, the dipole-dipole method was used because it obtained more data so as to see the potential distribution of hot water and subsurface constituent rocks in more detail, obtained the results of analysis from processing using RES2DINV that the resistivity value is 6.66 -23.5 Ωm which is thought to be a geothermal source, the rock formation that is considered to be related to the hot springs of Air Putih Village is located at (72.4 - 120) metres with a depth of (0.5 -18) metres. The rock layer has a resistivity value of (6.6 - 23.5 Ωm), which is characteristic of hot water because it has low resistance and is perpendicular to the hot spring. The existence of this weak zone indicates that the porosity will increase, causing hot water from the subsurface to appear as a geothermal manifestation, the hydrothermal distribution in the research area is uneven due to the unequal rock constituents, according to the geological map in the research area the area is a sihapas formation, where the sihapas formation consists of sedimentary rocks, sand, clastic, and siltstone. This research is recommended to develop the tourism potential of hot springs in Air Putih Village, Lebong.